IMPLEMENTATION STRATEGY OF MULTICULTURAL EDUCATION BASED ON ISLAMIC VALUES AT SMP SUMBARRANG - Azis; Ismail, Hilmi; Ismail (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
Multicultural education plays a vital role in promoting moderate and inclusive Islamic values, particularly in pluralistic school environments. This study explores the implementation strategies of multicultural education based on Islamic values at SMP Sumbarrang. Using a descriptive qualitative method, data were gathered through participatory observation, semi-structured interviews with 12 informants (teachers, principal, and students), and documentation analysis. The findings reveal that Islamic values such as tolerance (tasamuh), brotherhood (ukhuwah), justice (‘adl), and compassion (rahmah) align with the core principles of multicultural education. However, the implementation remains normative and lacks systematic integration into both learning activities and school programs. The study recommends the development of a multicultural-based Islamic education (PAI) curriculum, targeted teacher training, and enhanced collaboration among schools, parents, and communities. These efforts are essential to cultivating an educational environment that respects diversity. The study contributes to the advancement of a contextual Islamic education model suitable for plural societies. Pendidikan multikultural penting untuk menanamkan nilai-nilai Islam yang moderat dan inklusif, terutama di lingkungan sekolah yang plural. Penelitian ini bertujuan menganalisis strategi implementasi pendidikan multikultural berbasis nilai-nilai Islam di SMP Sumbarrang. Metode yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi partisipatif, wawancara semi-terstruktur terhadap 12 informan (guru, kepala sekolah, siswa), serta studi dokumentasi. Hasil penelitian menunjukkan bahwa nilai-nilai Islam seperti toleransi (tasamuh), persaudaraan (ukhuwah), keadilan (‘adl), dan kasih sayang (rahmah) selaras dengan prinsip pendidikan multikultural. Namun, implementasinya masih bersifat normatif dan belum terintegrasi secara sistematis dalam pembelajaran dan program sekolah. Oleh karena itu, diperlukan pengembangan kurikulum PAI berbasis multikultural, pelatihan guru, serta sinergi antara sekolah, orang tua, dan masyarakat. Temuan ini memberi kontribusi dalam pengembangan model pendidikan Islam yang kontekstual dan relevan dengan masyarakat majemuk.